2010
DOI: 10.1002/pd.2625
|View full text |Cite
|
Sign up to set email alerts
|

A mixture model of nuchal translucency thickness in screening for chromosomal defects: validation of a single operator dataset

Abstract: The use of the mixture model in a single operator dataset produces results compatible with the original study. The mixture model has thus been validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…In such cases, it can be rather difficult to interpret the CUSUM chart, and long‐term or retrospective use is limited because CUSUM must be restarted to determine whether a corrective action has been sufficient. Another consideration to mention is that CUSUM charts are sensitive to normality assumptions; in concordance with other large studies, our study found that this assumption was not sufficiently met.…”
Section: Discussionsupporting
confidence: 74%
“…In such cases, it can be rather difficult to interpret the CUSUM chart, and long‐term or retrospective use is limited because CUSUM must be restarted to determine whether a corrective action has been sufficient. Another consideration to mention is that CUSUM charts are sensitive to normality assumptions; in concordance with other large studies, our study found that this assumption was not sufficiently met.…”
Section: Discussionsupporting
confidence: 74%
“…Her family history was unremarkable. First‐trimester nuchal translucency thickness was 1.4 mm (55.8th centile), 4 and cell‐free fetal DNA test suggested a low risk of aneuploidy. Fetal echocardiography revealed the ductal anomalous origin of the left pulmonary artery (DOPA) associated with tetralogy of Fallot (TOF).…”
Section: Case Presentationmentioning
confidence: 97%
“…Her family history was unremarkable. First-trimester nuchal translucency thickness was 1.4 mm (55.8th centile), 4 22q11 deletion and copy number variation sequencing (CNV-seq) was offered but declined by the woman. As a result, the mother decided to terminate the pregnancy and refused an autopsy.…”
Section: Case Presentationmentioning
confidence: 99%